NT-proBNP level and left ventricle diameters before and after transcatheter closure of PDA and VSD - Devy Kusmira; Ria Nova; Achirul Bakri (Paediatrica Indonesiana, 2018)
Background Amino-terminal pro-B-type natriuretic peptide (NT-proBNP) levels before and after transcatheter closure may correlate with changes in left ventricular internal diameter end diastole (LVIDd) and end systole (LVIDs). Patent ductus arteriosus (PDA) and ventricular septal defect (VSD) are structural abnormalities which effects cardiac hypertrophy. Cardiac muscle stretching decreases after closure, followed by reduced left ventricle diameters and decreased NT-proBNP levels. Objective To analyze for possible correlations between NT-proBNP levels and left ventricle diameters before and after transcatheter closure. Methods Subjects were PDA and VSD patients who underwent transcatheter closure in the Pediatrics Department of dr. Moh Hoesin Hospital, Palembang, South Sumatera, from May 2016 to March 2017. Measurement of NT-proBNP levels and echocardiography were performed before closure, as well as one and three months after closure. Results There were 34 subjects (15 girls) with median age of 91.5 months. Median NT-proBNP levels were significantly reduced after closure: before closure 111.7pg/mL, one month after closure 62pg/mL, and three months after closure 39 pg/mL (P<0.05). Median LVIDd and LVIDs were also significantly reduced after closure [LVIDd: 39.5mm before, 34.5mm one mo after, and 32.5mm 3 mo after (P<0.05); LVIDs: 23.9mm before, 20.5mm 1 mo after, and 20.0mm 3 mo after (P<0.05)]. At one month after closure, there was a moderate positive correlation between NT-proBNP levels and LVIDd (r=0.432; P=0.011), but no correlation with LVIDs (r=0.287; P=0.100). At three months after closure, there was a significant moderate positive correlation between changes of NT-proBNP levels and changes of LVIDd (r=0.459; P=0.006), as well as LVIDs (r=0.563; P=0.001). Conclusion In pediatric PDA and VSD patients, NT-proBNP levels have a significant positive correlation with diastolic and systolic left ventricle diameters at three months after closure. Decreased NT-proBNP levels may be considered as a marker of closure effectiveness.